Megaspore Investigations of Selaginella Species from Sao Paulo, Brazil - Bauer, Dennise S.; Prado, Jefferson; Trovo, Marcelo; Coan, Alessandra I. [UNESP]; Stuetzel, Thomas; Schulz, Christian (Amer Fern Soc Inc, 2016)
The lycophyte genus Selaginella has a worldwide distribution with ca. 800 species. The genus is heterosporous and has ornamentation on the surface of both the megaspores and the microspores. Selaginella megaspore ornamentation is highly variable in both its macro- and microsculpture. Megaspore ornamentation is a species-specific morphological feature that can be used reliably for specimen identification. We present the first investigation of the megaspore surface of all 19 Selaginella species known from the state of Sao Paulo, Brazil, using scanning electronic microscopy (SEM). This study also includes Selaginella species that are invasive in Brazil. Based on the SEM analysis and high-resolution photographs, we provide detailed megaspore descriptions and an identification key for all species from Sao Paulo state. We also describe the proximal and distal pole ornamentation of the megaspores as well as the form and proportions of the trilete aperture.
Keywords: heterospory; lycophytes; ornamentation; South America; SEM